A bifunctional smart material: the synthesis of a metal-free black pigment for optoelectronic applications from an organic semiconducting molecular rod. Issue 1 (2nd January 2018) - Jones, Leighton; Luo, Xujun; Kazlauciunas, Algy; Lin, Long
Abstract : Purpose: This paper aims to synthesise and evaluate the properties of a novel smart material consisting of a metal-free organic black pigment with a unique chromophore for bifunctional applications in optoelectronics. Design/methodology/approach: A robust and highly efficient organic reaction, namely, a double [2 + 2] cycloaddition, was deployed to transform a rod-like structure for charge-transfer applications to a strongly conjugated light-absorbing molecule for both optical and electronic applications. Findings: The synthesis and characterisation of an air-stable metal-free black pigment is reported, which contains an unconventional donor–acceptor panchromatic chromophore with an absorption window spanning 600 nm; the compound was synthetically converted from an organic semiconducting molecular rod and retains strong charge-transfer properties. The chromophore comprises tetracyanoquinodimethane adduct on either side of a dithienothiophenyl core, capped with hexyl thiophenes that ensure solubility in common organic solvents. Its propensity to form excellent thin films on different substrates such as glass and paper, with a total opacity in organic solvent, gives it the potential for wide-ranging applications in organic optoelectronics. Research limitations/implications: The synthetic chemistry and fundamental properties are investigated in the present study, with more detailed treatments and analysis to be soon developed. One leading smart material is presented, with further derivatives under investigation. Practical implications: The work presented shows the possibility of converting structures from one application to another with relative ease, but how they retain properties for both, using well-known and facile conditions. Originality/value: The structures are novel and an enhanced air-stable organic panchromatic chromophore is reported for processing in common organic solvents.